2022
DOI: 10.3389/fpsyg.2022.857249
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Analysis of Digital Movement Assessment and ExerGame Scores for Parkinson's Disease Severity Estimation

Abstract: Neurodegenerative Parkinson's Disease (PD) is one of the common incurable diseases among the elderly. Clinical assessments are characterized as standardized means for PD diagnosis. However, relying on medical evaluation of a patient's status can be subjective to physicians' experience, making the assessment process susceptible to human errors. The use of ICT-based tools for capturing the status of patients with PD can provide more objective and quantitative metrics. In this vein, the Personalized Serious Game … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This approach enables the periodic assessments of users' performance on the game platform over an extended duration, thus facilitating the capture of more accurate and representative data. Previous research has primarily focused on utilizing in-game data from serious games for the purpose of cognitive screening [17,[20][21][22][23], and exergames for motor training [24][25][26], with occasional applications in physical health assessments [30,31]. In contrast, our proposed work addresses the challenge of designing a game platform that functions as both an intervention and an assessment tool for evaluating motor and cognitive abilities in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach enables the periodic assessments of users' performance on the game platform over an extended duration, thus facilitating the capture of more accurate and representative data. Previous research has primarily focused on utilizing in-game data from serious games for the purpose of cognitive screening [17,[20][21][22][23], and exergames for motor training [24][25][26], with occasional applications in physical health assessments [30,31]. In contrast, our proposed work addresses the challenge of designing a game platform that functions as both an intervention and an assessment tool for evaluating motor and cognitive abilities in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Mahboobeh et al examined the use of the Personalized Serious Game Suite and Intelligent Motor Assessment Tests from the i-PROGNOSIS platform for the objective assessment of Parkinson's disease stages [30]. The study demonstrated that machine learning classifiers can effectively utilize data from these tools to accurately infer the stage of the disease with a high accuracy rate (>90%).…”
Section: Physical Health Assessmentmentioning
confidence: 99%
“…This capability provides automated food volume estimation from just a single food image ( 82 ), facilitating the data input to the PROTEIN app and contributing toward the development of an accurate dietary assistant application. PROTEIN app acknowledges the effectiveness of health-related games to engage users in dealing with their health ( 83 , 84 ) and informing them about deterioration of symptoms in diseases ( 85 ), and thus, it also incorporates different dietary games. In this way, PROTEIN app fosters adherence to the suggested plans, making the app fun to use, and providing the means for encouragement and/or (re)education on nutritional value of the various food groups toward the adoption of a healthy and balanced diet.…”
Section: Methodsmentioning
confidence: 99%
“…Another alternative solution to the Kinect Sensor V2 is MentorAge, a depth RGB (Red, Green, Blue) image sensor tracking system that operates on the Android system and uses infrared 3D capturing technology. It can detect a maximum of 4 people in a single room within a range of 0.6 to 5 m and has proven its capabilities and potentialities in real-life scenarios [80,85,86]. No additional equipment is thought to be used compared with the current version of MS-FIT.…”
Section: Plans For Future Studiesmentioning
confidence: 99%